2008
DOI: 10.1002/jmri.21489
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and optimization of parameter accuracy in dynamic contrast‐enhanced MRI

Abstract: Purpose: To present a modified pharmacokinetic model for improved parameter accuracy and to investigate the influence of an inaccurate arterial input function (AIF) on dynamic contrast-enhanced (DCE)-MRI parameter estimates of the transfer constant (K trans ), blood volume (v p ), and interstitial volume (v e ). Materials and Methods:Tissue uptake curves were simulated over a large range of physiological values and analyzed for different AIF measurement errors and temporal resolutions. The AIF measurement was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 26 publications
4
91
0
Order By: Relevance
“…It has been shown that error in estimating the initial AIF amplitude can propagate into the resulting parameter estimates (90) and various innovative approaches have been proposed for sampling the AIF, such as the use of a low-dose prebolus (91) and the MR signal phase (92). However, accurate measurement of the AIF from DCE MRI data can be challenging in situations such as the absence of a suitable artery in the imaging field of view, low signal-tonoise, and partial volume effects for small arteries.…”
Section: Reference Region (Rr) Methodsmentioning
confidence: 99%
“…It has been shown that error in estimating the initial AIF amplitude can propagate into the resulting parameter estimates (90) and various innovative approaches have been proposed for sampling the AIF, such as the use of a low-dose prebolus (91) and the MR signal phase (92). However, accurate measurement of the AIF from DCE MRI data can be challenging in situations such as the absence of a suitable artery in the imaging field of view, low signal-tonoise, and partial volume effects for small arteries.…”
Section: Reference Region (Rr) Methodsmentioning
confidence: 99%
“…This linearity can be assumed to be valid for other scanners and scan protocols. Differences in the choice of time points in the acquisition protocol can infl uence the accuracy with which model parameters are determined and may lead to a bias ( 35,36 ). Changes in injection protocol may have a similar effect (36)(37)(38), even though the AIF is explicitly taken into account in the analysis.…”
Section: Roi Analysis Parametersmentioning
confidence: 99%
“…The main rationale of our approach was to avoid unreliability and inaccuracy of the PK‐model‐based method. It has been established that wide variability in estimating arterial input function leads to substantial deviations in calculating TP and BV parameters 45, 46. Moreover, PK modeling is significantly influenced by B 1 field inhomogeneity.…”
Section: Discussionmentioning
confidence: 99%